2018
DOI: 10.1371/journal.pone.0208266
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in western corn rootworm (Coleoptera: Chrysomelidae) susceptibility to Cry3 toxins in Nebraska

Abstract: Repeated use of field corn (Zea mays L.) hybrids expressing the Cry3Bb1 and mCry3A traits in Nebraska has selected for field-evolved resistance in some western corn rootworm (WCR; Diabrotica virgifera virgifera LeConte) populations. Therefore, this study was conducted to characterize spatial variation in local WCR susceptibility to Cry3Bb1 and mCry3A traits in Keith and Buffalo counties, Nebraska, and determine the relationship between past management practices and current WCR susceptibility. Adult WCR populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 47 publications
3
67
0
Order By: Relevance
“…This would explain why, in our experiment, previous management among focal fields and surrounding fields differed but rootworm resistance to Cry3Bb1 did not ( Table 2, Fig 6). However, it is worth noting that an experiment in Nebraska, which also examined resistance to Cry3 in local landscapes, concluded that individual field-level selection was a major contributor to resistance levels [34]. Indeed, most fields in our experiment, focal fields and surrounding fields, had experienced some level of selection to Cry3Bb1.…”
Section: Plos Onementioning
confidence: 71%
See 2 more Smart Citations
“…This would explain why, in our experiment, previous management among focal fields and surrounding fields differed but rootworm resistance to Cry3Bb1 did not ( Table 2, Fig 6). However, it is worth noting that an experiment in Nebraska, which also examined resistance to Cry3 in local landscapes, concluded that individual field-level selection was a major contributor to resistance levels [34]. Indeed, most fields in our experiment, focal fields and surrounding fields, had experienced some level of selection to Cry3Bb1.…”
Section: Plos Onementioning
confidence: 71%
“…For example, computer modeling work on Helicoverpa zea, has shown that clusters of up to 20 contiguous fields where Bt use was high led to rapid evolution of resistance due to pest movement [49]. Additionally, Cry3Bb1-resistant western corn rootworm populations in Nebraska were found in cornfields with no history of Cry3Bb1 selection [34]. Like many biological 2016, and C) 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the US western Corn Belt, maize production under irrigation has often been more profitable than other available crops, which discourages the adoption of crop rotation. The demand for maize is high for livestock operations and ethanol production, leading to higher adoption of continuous maize (maize planted consecutively for two or more years) . This can lead to build‐up of WCR densities, making the annual management of this pest a considerable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, for varying reasons, not every grower can utilize this management practice. The use of corn hybrids expressing Bacillus thuringiensis (Bt) Berliner has been widely used against corn rootworms since 2003 (Vaughn et al 2005) and resistance evolution to commercially available Bt traits by the western corn rootworm has been documented in the field (Gassmann et al 2011, Wangila et al 2015, Jakka et al 2016, Zukoff et al 2016, Ludwick et al 2017, Reinders et al 2018. Recently, field-evolved resistance of northern corn rootworm to Bt corn has been reported (Calles-Torrez et al 2018.…”
mentioning
confidence: 99%